(3cJGH aj GdJGQjNs - (3YKeGf Hf EHQGgje GdfGHdSj GdUaOj, aNQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3aGfJgi Hg GdUjO Edi CQV GdYQjT aWQO CeGeg hMT cHjQ aWdHg Gdedc hGTJZd cd MGLH hebOe hCejQ GjVkG jJUjO s
(3BNQgG (B:s
(3hbGd QShd Gddg Udi Gddg Ydjg hSde cd ejJ jNJe Ydi Yedg EdG GdPi jehJ eQGHWkG aEfg jfeh dg Yedg Edi jhe GdbjGeI hjCef aJfI GdbHQ Je Pdc hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B61(3C (B- (3U(B70(3Cs
(3GdeNWhW bWYI ef BNQ GdcJGH JJVef HYV CNHGQ GdebhbS ai UjOg haJM GdeSdejf OejGW hHGH ai aVGFdgG hBNQ ai TWG hQedIs
(3JdGI ai gPG GdeLehY YfhGf GdcJGH GdJGdi (B: (3cJGH CfjS GdLdjS ai CNHGQ JfjS hGdLRGFQ JCdja TeS GdOjf eMeO Hf TgGH GdOjf CMeO GdeYQha H GHf HSGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B202 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B249s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe (B5 - (3U (B158 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs